To Study the Effect of MAXX Training on Strength, Speed and Agility of Basketball Wheelchair Players - hasan daneshmandi; masoud Mirhashemi; pegah Rahmani (Sport Sciences and Health Research)
The aim of this research was to study the effect of Maxx strength training which was the combination of maximal strength training and explosive power) on the increase of speed, strength and agility of disabled athletes. 20 paraplegic subjects were selected randomly out of 52 elite basketball wheelchair players and then they were divided into two groups: experimental group (n=10, age 28.1± 2.55, sitting height 89.3± 14) and control group (n=10, age 29.2 ±2.55, sitting height 87.7±9.04). Demographic and medical data were collected by interviews, questionnaire and medical history records. Then, speed, agility and maximum strength of subjects were measured in pretest and posttest respectively by propelling wheelchair across the dia meter of basketball field, zigzag test and bench chest press. Experimental group performed the Maxx training protocol for 6 weeks and 3 sessions per week. Control group performed ordinary training. The results of posttest were analyzed by SPSS (P? 0.01). The findings showed that Maxx training protocol for 6 weeks significantly influenced subjects’ strength and agility. These results emphasized the need to perform Maxx training protocol which had previously been effective in healthy athletes. Because of the training and skill demands of basketball wheelchair players, it can be suggested that trainers apply the combination of strength training and explosive power for paraplegic players because they can be performed in the sitting position on wheelchair.